2019
DOI: 10.18043/ncm.80.6.332
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Chronic Health Conditions Among Adults Released From the North Carolina Prison System, 2015-2016

Abstract: background In the United States each year nearly 570,000 people return from state prisons to the community. Prevalence data of chronic health problems for this population are lacking, impeding planning of health care programs to serve people with chronic conditions who are re-entering the community. method We used medication dispensing records as a proxy for diagnoses in assessing the prevalence of 10 major and 20 substituent health conditions among incarcerated people released from the North Carolina state pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…The quality of the mental health care female prisoners receive is a pressing concern (Chandler, 2003), especially since a North Carolina study reported that the “prevalence of comorbid chronic medical problems was particularly high among those [inmates] with mental health diagnoses” (Rosen et al, 2019, p. 337). Consider, for example, a situation where a female inmate with a history of bipolar disorder died after four days of grossly incompetent and callous treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The quality of the mental health care female prisoners receive is a pressing concern (Chandler, 2003), especially since a North Carolina study reported that the “prevalence of comorbid chronic medical problems was particularly high among those [inmates] with mental health diagnoses” (Rosen et al, 2019, p. 337). Consider, for example, a situation where a female inmate with a history of bipolar disorder died after four days of grossly incompetent and callous treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to needing specialized care, inmates with chronic conditions have medical needs that require vigilant monitoring and higher diagnostic consideration (Rosen et al, 2019). Studies have found that some correctional facilities do not regularly monitor chronic illnesses according to clinical best practices (Rosen et al, 2019; Wilper et al, 2009). In Fraher v. Heyne (2014 ) , the plaintiff believed that a correctional physician overlooked complications with her heart condition.…”
Section: Methodsmentioning
confidence: 99%
“…This secondary analysis of de-identified data was approved by the University of North Carolina Institutional Review Board [IRB 16-2040, PI: Ashkin] and the North Carolina Department of Public Safety (DPS) Human Subjects Research Committee [HSRC # 1611-01, PI: Ashkin]. Additional study data and methodology are reported elsewhere (Rosen et al , 2019). A list of all unique medications dispensed between July 1, 2015 and June 30, 2016 was reviewed for relevance to clinical menopause management.…”
Section: Methodsmentioning
confidence: 99%
“…They also have higher rates of hypertension, heart disease, lung disease, depression, and post-traumatic stress disorder (PTSD) (Massoglia 2008; Wilper et al 2009). Having to manage multiple chronic health conditions is also common among those being released (Rosen et al 2019). In two prospective cohort studies, people released from prisons report an increased number of chronic conditions, a decrease in their self-reported health status, and a higher risk of reporting a severe health impairment relative to peers who were not incarcerated during the study period (Massoglia 2008; Schnittker and John 2007).…”
Section: The Health Of Those Under Community Supervision: Current Res...mentioning
confidence: 99%